The effects of microphone spacing on auditory localization - Maxon, A.B.; Mazor, M. (International Journal of Audiology, 1977)
The localization ability of 10 normally hearing adults was determined under varying microphone separations and varying sound source azimuths. The stimuli (white noise bursts) were prerecorded, after being transduced through 'body' hearing aids and then played to the subjects over headphones. Results indicated that there was an improvement in localization ability for all azimuth conditions when the microphones were spaced wider than 12.7 cm apart (15.2-30.5 cm). The smaller the separations (5.5-12.7 cm), the poorer the localization. Localization was always poorer at 30° azimuth (the smallest used) than at any of the other azimuths (0° 30° 60° 90° right and left), regardless of microphone spacing. Implications are made about the relation of these findings to the use of binaural body aids on infants and young children. © 1977 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: Acoustic Stimulation; Audiometry; Auditory Perception; Auditory localization; Binaural amplification; Female; Hearing Aids; Human; Male; Noise; Pediatric amplification; audiology; binaural hearing; child; dept.cmd; directional hearing; methodology; microphone